A high-hardness anti-glare film and preparation method thereof
By using a combination of inorganic particles of various particle sizes and shapes, an anti-glare film coating with high hardness and high wear resistance is solved, and the problem of difficulty in taking into account both hardness, wear resistance and surface roughness in the prior art is achieved, and an efficient and economical anti-glare film preparation is achieved.
Patent Information
- Application Number
- CN202111661125.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The existing high-hardness anti-glare films are difficult to take into account high hardness, high wear resistance and low surface roughness.
An anti-glare particle combination including 1-6 μm spherical silica particles, 0.1-0.5 μm nanoalumina particles and 20-70 nm nanosilicon dioxide particles was used to form an anti-glare coating of 4-10 μm through a one-step coating process.
High hardness (at least 4H) and high wear resistance (at least 5000 steel wool wear tests without scratches) are achieved while maintaining low surface roughness and good cost advantages.
Smart Images

Figure CN116410508B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-glare films, in particular to an anti-glare film with high hardness and a preparation method thereof. Background Art
[0002] With the development of technology, electronic display devices no longer need to meet basic display performance such as high definition / high color gamut, but also need to meet more touch interaction scenarios. For example, in the electronic teaching in the field of modern teaching, the electronic blackboard needs to meet the writing requirements of chalk and fountain pens; in conference scenes, the demand for touch performance of the display to achieve faster communication has become an inevitable trend. However, the display device in this scenario requires higher hardness and wear resistance. At the same time, the "glare" effect formed by the display device during use will significantly cause differences in brightness and contrast, reduce image recognition, and affect people's physical and mental health in a long-term environment. In this regard, the popularization of a high-hardness, high-wear-resistant anti-glare film is particularly important.
[0003] To solve the problem of high hardness and anti-glare of display screens, anti-glare (AG) glass is used on the one hand, but this method is greatly limited by the physical properties of glass (fragility, bulkiness) and cost issues. On the other hand, high-hardness anti-glare film is used externally, which is inexpensive and has controllable performance.
[0004] Patents CN112485853A and CN109810555A use large particles with an average particle size of 10μm and 15μm or more to prepare high-hardness anti-glare films, respectively. The coating thickness is above 20μm, and the hardness of the anti-glare film meets 5-6H, but the surface roughness is large, which is not conducive to wear resistance and has a rough feel. Patent CN113166586A uses small particles of about 4μm to prepare an anti-glare film with a hardness of 5H, but its process is relatively complicated, requiring a high-hardness coating of more than 10μm and an anti-glare coating of more than 2μm. The surface roughness is low but the wear resistance is poor. Among the current patents for high-hardness anti-glare films, there are few products that can well balance high hardness, high wear resistance and low surface roughness.
[0005] Therefore, it is necessary to design an anti-glare film with high hardness and high wear resistance. Summary of the invention
[0006] In order to solve the problem that the existing anti-glare film cannot take into account both high hardness and high wear resistance, the present invention provides a high-hardness anti-glare film and a preparation method thereof. The high-hardness anti-glare film has both high hardness and high wear resistance, solving the problem that the existing anti-glare film cannot take into account both high hardness and high wear resistance.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0008] The invention provides a high-hardness anti-glare film, which comprises a substrate and an anti-glare coating.
[0009] Furthermore, the anti-glare coating includes anti-glare particles, and the anti-glare particles include first anti-glare particles, second anti-glare particles and third anti-glare particles.
[0010] Furthermore, the particle size of the first anti-glare particles is 1-6 μm, accounting for 41.2%-54% of the total content of anti-glare particles; the particle size of the second anti-glare particles is 0.1-0.5 μm, accounting for 0.5%-0.6% of the total content of anti-glare particles; the particle size of the third anti-glare particles is 20-70 nm, accounting for 45.5%~58.2% of the total content of anti-glare particles; the contents are expressed in percentage by weight.
[0011] The total content of the anti-glare particles is the total content of the first anti-glare particles, the second anti-glare particles, and the third anti-glare particles.
[0012] The particle size D of the first anti-glare particles 50 is 2 μm, and the particle size D of the second anti-glare particles is 50 is 0.3 μm, and the particle size D of the third anti-glare particles is 50 It is 40nm.
[0013] Furthermore, the first anti-glare particles, the second anti-glare particles and the third anti-glare particles are all inorganic particles.
[0014] Furthermore, the first anti-glare particles are spherical particles.
[0015] Furthermore, the sphericity of the first anti-glare particles is 100%.
[0016] Furthermore, the first anti-glare particles are preferably silicon dioxide particles, and the second anti-glare particles and the third anti-glare particles can be silicon dioxide particles, aluminum oxide particles, or a combination thereof.
[0017] Furthermore, the dry film thickness of the anti-glare coating is 4-10 μm.
[0018] Furthermore, the substrate is selected from one of polyethylene terephthalate (PET), triacetyl cellulose (TAC), polycarbonate (PC), or polymethyl methacrylate (PMMA).
[0019] Furthermore, the substrate is a transparent substrate.
[0020] Furthermore, the thickness of the substrate is preferably 75 to 250 μm.
[0021] Furthermore, the anti-glare coating is formed by coating and curing an anti-glare coating liquid.
[0022] Furthermore, the anti-glare coating liquid includes the following ingredients: 24.4%-33.5% of acrylic prepolymer, 5.6%-9.1% of acrylic monomer, 2.8%-3.3% of photoinitiator, 0.3% of leveling agent, 17.0%-20.6% of anti-glare particles, and 39.4%-46.5% of organic solvent, and the percentages are weight percentages; the 17.0%-20.6% anti-glare particles include 7.0-11.1% of first anti-glare particles, 0.1% of second anti-glare particles, and 8.4-9.9% of third anti-glare particles.
[0023] Further, the anti-glare coating liquid includes the following ingredients: 24.4%-33.5% of acrylic prepolymer, 5.6%-9.1% of acrylic monomer, 2.8%-3.2% of photoinitiator, 0.3% of leveling agent, 18.4%-20.6% of anti-glare particles, 39.4%-44.4% of organic solvent, and the percentages are weight percentages; the 18.4%-20.6% anti-glare particles include 9.9-11.1% of first anti-glare particles, 0.1% of second anti-glare particles, and 8.4-9.4% of third anti-glare particles. Further, the dry film thickness of the anti-glare coating is 7-8 μm. The above technical solution includes embodiments 1-3.
[0024] Furthermore, the acrylic prepolymer is a nine-functional polyurethane acrylic resin oligomer. The acrylic monomer is a six-functional acrylate monomer. The organic solvent is ethyl acetate. The photoinitiator is TPO or 184. The leveling agent is BYK333.
[0025] Furthermore, the first anti-glare particles are spherical silica particles with a particle size D 50 The second anti-glare particle is nano-alumina, with a particle size of D 50 The third anti-glare particle is nano-silicon dioxide with a particle size of 0.3 μm. 50 It is 40nm.
[0026] On the other hand, the present invention also provides a method for preparing the high-hardness anti-glare film, the method comprising the following steps:
[0027] (1) preparing an anti-glare coating liquid: 24.4%-33.5% of acrylic prepolymer, 5.6%-9.1% of acrylic monomer, 2.8%-3.3% of photoinitiator, 0.3% of leveling agent, 17.0%-20.6% of anti-glare particles, and 39.4%-46.5% of organic solvent, wherein the percentages are by weight;
[0028] (2) The anti-glare coating liquid is uniformly coated on a transparent substrate by roller coating or the like, and after baking and drying, UV curing is performed to finally obtain a high-hardness, high-wear-resistant anti-glare film.
[0029] Among them, the anti-glare particles include first anti-glare particles, second anti-glare particles and third anti-glare particles. The particle size of the first anti-glare particles is 1-6μm, accounting for 41.2%-54% of the total content of anti-glare particles; the particle size of the second anti-glare particles is 0.1-0.5μm, accounting for 0.5%-0.6% of the total content of anti-glare particles; the particle size of the third anti-glare particles is 20-70nm, accounting for 45.5%~58.2% of the total content of anti-glare particles; the content is weight percentage.
[0030] Wherein, the acrylic prepolymer is selected from one or a combination of a ten-functional polyurethane acrylic resin oligomer or a nine-functional polyurethane acrylic resin oligomer.
[0031] Compared with the prior art, the high-hardness anti-glare film provided by the present invention has the following beneficial effects:
[0032] 1. The anti-glare film provided by the present invention is prepared by using anti-glare particles with high sphericity, thereby achieving higher surface hardness and wear resistance of the anti-glare film;
[0033] 2. The anti-glare film provided by the present invention has anti-glare particles of small size and a high total particle addition amount. The coating surface has a low surface roughness (≤0.5 μm) and a high particle filling density, which further improves the hardness and wear resistance of the coating.
[0034] 3. The anti-glare film provided by the present invention is prepared by a one-step method, and the process is simple; the overall haze is low, and it has good compatibility with anti-glare performance and light transmission performance; the coating thickness is low, and it has good cost advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the structure of the high-hardness anti-glare film provided by the present invention;
[0036] Figure 2 Schematic diagram of the structure of an anti-glare film prepared from irregular spherical particles in a comparative example of the present invention;
[0037] Figure 3A and Figure 3B The surface photos of Example 1 before wear and after 5000 times of wear of steel wool are shown respectively;
[0038] Figure 4A and Figure 4B The surface photos of Comparative Example 1 before abrasion and after 100 times of abrasion of steel wool are shown respectively;
[0039] Figure 5A and Figure 5B The following are surface photos of comparative example 3 before abrasion and after 100 times of abrasion with steel wool.
[0040] Explanation of the numbers in the figure: 1-substrate; 2-anti-glare layer; 3-first anti-glare particles; 4-second anti-glare particles; 5-third anti-glare particles. DETAILED DESCRIPTION
[0041] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the preferred embodiments of the present invention are described in detail with reference to the drawings as follows:
[0042] like Figure 1 As shown, the present invention provides a high-hardness anti-glare film, which comprises, from bottom to top, a substrate layer 1 and an anti-glare layer 2. The anti-glare layer 2 comprises anti-glare particles; the anti-glare particles comprise first anti-glare particles 3, second anti-glare particles 4 and third anti-glare particles 5.
[0043] like Figure 2 As shown, the surface of the anti-glare film prepared by the irregularly shaped first anti-glare particles in the comparative example is relatively rough and sharp. In the hardness and wear resistance tests, the sharp parts of the irregular morphology of the first anti-glare particles will be destroyed first, and the hardness and wear resistance are poor.
[0044] Taking Example 1, Comparative Example 1 and Comparative Example 3 as examples, the surface roughness of the anti-glare films of the three are similar, but their surface structures are significantly different from microscopic observation. The surface of the anti-glare film of the irregular spherical particles in the comparative example appears to be rougher, and the particle distribution and protrusions are more obvious (such as Figure 4A and Figure 5A At the same time, after the coating surface was abraded by steel wool 100 times, the protruding particles on the coating surface were severely worn and obvious scratches appeared (as shown in Figure 4B and Figure 5B shown).
[0045] The surface of the anti-glare film prepared by the spherical anti-glare particles in the embodiment is smoother, and the transition between the glue layers of the particles is smooth and round (such as Figure 3A After 5000 times of abrasion with steel wool, the anti-glare coating surface showed little difference before and after abrasion, with only slight signs of wear (such as Figure 3B shown).
[0046] Example 1
[0047] The present invention provides a high-hardness anti-glare film, which includes a substrate and an anti-glare coating. The anti-glare coating includes anti-glare particles, which include first anti-glare particles, second anti-glare particles and third anti-glare particles, wherein the first anti-glare particles are spherical particles, and the anti-glare coating is formed by coating and curing an anti-glare coating liquid. The preparation method of the high-hardness anti-glare film is as follows.
[0048] 1. Preparation of anti-glare coating liquid
[0049] 25.2% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.3% of six-functional acrylate monomer (product of Sartomer), 3.2% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 11.1% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 50 2 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 9.4% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 44.4% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0050] 2. Anti-glare coating (anti-glare layer for short) coating
[0051] The anti-glare coating liquid (referred to as coating liquid) is evenly coated on a 100 μm thick PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain a high-hardness anti-glare film (referred to as anti-glare film) with a dry film thickness of 7-8 μm.
[0052] Example 2
[0053] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0054] 1. Preparation of anti-glare coating liquid
[0055] 33.5% of nine-functional polyurethane acrylic resin polymer (product of DSM), 5.6% of six-functional acrylate monomer (product of Sartomer), 2.8% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 9.9% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 502 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., flat particle size D 50 0.3 μm), 8.4% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 39.4% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0056] 2. Anti-glare coating
[0057] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 7-8 μm.
[0058] Example 3
[0059] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0060] 1. Preparation of anti-glare coating liquid
[0061] 24.4% of nine-functional polyurethane acrylic resin polymer (product of DSM), 9.1% of six-functional acrylate monomer (product of Sartomer), 3.1% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 10.8% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 50 2 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 9.1% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 43.1% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0062] 2. Anti-glare coating
[0063] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 7-8 μm.
[0064] Example 4
[0065] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0066] 1. Preparation of anti-glare coating liquid
[0067] 26.3% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.6% of six-functional acrylate monomer (product of Sartomer), 3.3% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 7.0% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 50 2 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 9.9% of the third anti-glare particles - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 46.5% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0068] 2. Anti-glare coating
[0069] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 7-8 μm.
[0070] Example 5
[0071] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0072] 1. Preparation of anti-glare coating liquid
[0073] 25.2% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.3% of six-functional acrylate monomer (product of Sartomer), 3.2% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 11.1% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 50 2 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 9.4% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 44.4% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0074] 2. Anti-glare coating
[0075] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 4-5 μm.
[0076] Example 6
[0077] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0078] 1. Preparation of anti-glare coating liquid
[0079] 25.2% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.3% of six-functional acrylate monomer (product of Sartomer), 3.2% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 11.1% of the first anti-glare particles - spherical silica particles (Ningbo Gexin New Energy Technology Co., Ltd., particle size D 50 2 μm, sphericity 100%), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 9.4% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 44.4% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0080] 2. Anti-glare coating
[0081] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 9-10 μm.
[0082] Comparative Example 1
[0083] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0084] 1. Preparation of anti-glare coating liquid
[0085] 27.6% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.9% of six-functional acrylate monomer (product of Sartomer), 3.4% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 2.9% of the first anti-glare particles - irregular spherical silica particles (Grace, particle size D 50 3.7 μm), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D50 0.3 μm), 10.3% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 48.5% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0086] 2. Anti-glare coating
[0087] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 4-5 μm.
[0088] Comparative Example 2
[0089] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0090] 1. Preparation of anti-glare coating liquid
[0091] 27.6% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.9% of six-functional acrylate monomer (product of Sartomer), 3.4% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 2.9% of the first anti-glare particles - irregular spherical silica particles (Grace, particle size D 50 5.3 μm), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 10.3% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 48.5% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0092] 2. Anti-glare coating
[0093] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 4-5 μm.
[0094] Comparative Example 3
[0095] The high-hardness anti-glare film provided in Example 1 is prepared by the following method.
[0096] 1. Preparation of anti-glare coating liquid
[0097] 27.0% of nine-functional polyurethane acrylic resin polymer (product of DSM), 6.7% of six-functional acrylate monomer (product of Sartomer), 3.4% of photoinitiator TPO (product of BASF), 0.3% of leveling agent (product of BYK), 4.8% of the first anti-glare particles - irregular spherical silica particles (Evonik, particle size D 50 7 μm), 0.1% of the second anti-glare particles - nano-alumina (Nantong Jiangshan New Energy Technology Co., Ltd., particle size D 50 0.3 μm), 10.1% of the third anti-glare particle - nano silicon dioxide (Evonik, particle size D 50 is 40nm), and 47.6% of an organic solvent ethyl acetate are fully stirred and mixed to obtain an anti-glare coating liquid.
[0098] 2. Anti-glare coating
[0099] The coating liquid is evenly coated on a 100 μm PET substrate by roller coating or the like, baked at 85° C. for 5 min, and after the surface is dried, UV curing is performed to obtain an anti-glare film with a coating dry film thickness of 4-5 μm.
[0100] The formulas of the anti-glare coating liquids of the anti-glare films provided in the examples and comparative examples of the present invention are shown in Table 1-1 and Table 1-2.
[0101] Table 1-1 Formula of the anti-glare coating liquid of the anti-glare film provided in Example 1-6
[0102]
[0103] Table 1-2 Formula of the anti-glare coating liquid of the anti-glare film provided by Comparative Examples 1-3
[0104] project Comparative Example 1 Comparative Example 2 Comparative Example 3 Nine official polyurethane acrylic resin polymer 27.6% 27.6% 27.0% Hexafunctional acrylate monomer 6.9% 6.9% 6.7% TPO Photoinitiator 3.4% 3.4% 3.4% Leveling agent BYK333 0.3% 0.3% 0.3% The third anti-glare particle 10.3% 10.3% 10.1% Solvents 48.5% 48.5% 47.6% The first anti-glare particle 2.9% 2.9% 4.8% Second anti-glare particles 0.1% 0.1% 0.1% Total content 100% 100% 100%
[0105] The main properties of the anti-glare films provided in the embodiments and comparative examples of the present invention are tested using the following test methods.
[0106] (1) Transmittance / haze: The total light transmittance and haze of each anti-glare film were measured using an NDH7000 haze meter manufactured by Nippon Denshoku.
[0107] (2) Hardness: The pencil hardness of each anti-glare film was measured under a load of 500 g using a pencil hardness tester. The pencil used was a product of Mitsubishi Corporation.
[0108] (3) Wear resistance: The wear resistance of each anti-glare film was measured using an abrasion tester manufactured by Jinliang Industrial Co., Ltd. Steel wool #0000 was used for the abrasion test, with a load of 1000g. The wear resistance of the anti-glare film was determined by testing the number of times the film surface was abraded without scratches.
[0109] (4) Glossiness: The 60° reflective glossiness of the surface of each anti-glare film was measured using a KESGA gloss meter.
[0110] (5) Roughness: The surface roughness of each anti-glare film was measured using a portable surface roughness measuring instrument produced by Mitutoyo of Japan;
[0111] (6) Anti-glare performance: The present invention mainly uses a point light source to illuminate the anti-glare film at 60°, and observes the degree of scattering of the light shadow at the center of the point light source. The greater the degree of scattering of the light shadow, the better the anti-glare performance. The specific evaluation criteria for the anti-glare performance are as follows:
[0112] If the light shadow is completely invisible, the anti-glare performance is rated as "excellent";
[0113] If the light shadow is slightly visible, the anti-glare performance is rated as "good"
[0114] If the light shadow is clearly visible, there is basically no anti-glare performance and it is counted as "unqualified";
[0115] The performance test results of the embodiments and comparative examples are shown in Table 2 below.
[0116] Table 2 Performance test results of the anti-glare films provided by Examples 1 to 6 and Comparative Examples 1 to 3
[0117]
[0118]
[0119] Table 3 Parameter changes of Examples 1 to 6 and Comparative Examples 1 to 3
[0120]
[0121] From the data in Table 2, it can be seen that the surface hardness and wear resistance of the anti-glare film are directly related to the structural morphology of the particles. Compared with the anti-glare film prepared from the spherical anti-glare particles in the embodiment and the anti-glare film prepared from the irregular spherical anti-glare particles in the comparative example, at the same thin coating thickness (4-5μm), the hardness of the comparative anti-glare film is only 3H, and the optimal steel wool wear resistance is only about 100 times; while the hardness of the embodiment is at least 4H, and the wear resistance is at least 2500 times. At the same time, by increasing the coating thickness of the embodiment, the hardness can be effectively increased to 6H, and the wear resistance can achieve 5000 times without scratches. This is because the coating surface formed by spherical particles is rounded, while the coating surface formed by irregular spherical particles is rough, and the sharp parts are easily destroyed first in the hardness and wear resistance tests.
[0122] The anti-glare film provided by the present invention adopts small-size inorganic particles as anti-glare particles, and the coating surface has a lower surface roughness; at the same time, two kinds of nano-scale anti-glare particles are used as auxiliary, the overall particle addition amount is large, and the coating surface and interior have a large particle filling degree, which helps to further improve the surface hardness and wear resistance.
[0123] The anti-glare film provided by the present invention has a total coating thickness of only 7-8 μm at a hardness of 6H, and adopts a one-step coating process, which has a simple process and good compatibility with cost factors.
[0124] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A high-hardness anti-glare film, characterized in that: The high-hardness anti-glare film comprises a substrate and an anti-glare coating; the anti-glare coating comprises anti-glare particles, and the anti-glare particles comprise first anti-glare particles, second anti-glare particles and third anti-glare particles; the particle size of the first anti-glare particles is 1-6 μm, the particle size of the second anti-glare particles is 0.1-0.5 μm, and the particle size of the third anti-glare particles is 20-70 nm; the first anti-glare particles are spherical particles; the first anti-glare particles are silicon dioxide particles, and the second anti-glare particles and the third anti-glare particles are one of silicon dioxide particles or aluminum oxide particles or a combination thereof; the anti-glare coating is composed of The anti-glare coating liquid is formed after coating and curing, and the anti-glare coating liquid includes the following components: 24.4%-33.5% of acrylic prepolymer, 5.6%-9.1% of acrylic monomer, 2.8%-3.3% of photoinitiator, 0.3% of leveling agent, 17.0%-20.6% of anti-glare particles, 39.4%-46.5% of organic solvent, and the percentages are weight percentages; the 17.0%-20.6% anti-glare particles include 7.0-11.1% of first anti-glare particles, 0.1% of second anti-glare particles, and 8.4-9.9% of third anti-glare particles.
2. The high-hardness anti-glare film according to claim 1, characterized in that: The particle size D of the first anti-glare particles 50 is 2 μm, and the particle size D of the second anti-glare particles is 50 is 0.3 μm, and the particle size D of the third anti-glare particles is 50 It is 40nm.
3. The high-hardness anti-glare film according to claim 1, characterized in that: The dry film thickness of the anti-glare coating is 4-10 μm, the substrate is selected from one of polyethylene terephthalate, triacetyl cellulose, polycarbonate or polymethyl methacrylate, and the substrate is a transparent substrate.
4. The high-hardness anti-glare film according to claim 1, characterized in that: The anti-glare coating liquid includes the following ingredients: 24.4%-33.5% of acrylic prepolymer, 5.6%-9.1% of acrylic monomer, 2.8%-3.2% of photoinitiator, 0.3% of leveling agent, 18.4%-20.6% of anti-glare particles, and 39.4%-44.4% of organic solvent, and the percentages are weight percentages; the 18.4%-20.6% anti-glare particles include 9.9-11.1% of first anti-glare particles, 0.1% of second anti-glare particles, and 8.4-9.4% of third anti-glare particles.
5. The method for preparing a high-hardness anti-glare film according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) Preparing anti-glare coating liquid; (2) The anti-glare coating liquid is evenly coated on the substrate by roller coating, and after baking and drying, UV curing is performed to finally obtain a high-hardness anti-glare film.
Citation Information
Patent Citations
High-hardness and anti-dazzle hardening layer coating liquid and hardening film
CN109810555A
Resin composition for Anti-glare coating and Anti-glare coating film prepared thereby
CN113166586A
High-wear-resistance and low-flash-point anti-glare film and preparation method thereof
CN112375243A
Chalk writable anti-dazzle film
CN112485853A